The protumorigenic enzyme GPAT2 inhibits arachidonic acid-triggered apoptosis in breast cancer - Ferremi, Fiorella J. (2024)
Abstract Background Cancer is a significant health challenge and the leading cause of mortality globally. Tumor cells use multiple mechanisms to acquire their distinctive capacity for uncontrolled proliferation, one of which is the evasion of apoptosis. It has been shown that in breast, colon, and liver cancer, evasion of apoptosis is associated with the overexpression of enzymes that metabolize arachidonic acid (AA) because free AA is a strong inducer of apoptosis. Glycerol−3-phosphate acyltransferase 2 (GPAT2) is a key enzyme in AA metabolism and is highly expressed in breast and colon cancer, where it promotes the development of essential tumor features. Methods In this work, a model of GPAT2 silencing in the human breast cancer-derived cell line MDA-MB-231 was used, and the cells were exposed to exogenous AA. The role of GPAT2 in AA-induced cell death was studied using MTT and TUNEL assays and measurements of caspase activity. The underlying molecular mechanism of cell death was assessed by qRT‒PCR. Results The results showed that AA reduced cell viability only in GPAT2-silenced cells, and that this cell death was a consequence of an apoptotic process involving BNIP3 overexpression. Additionally, it was demonstrated that GPAT2 silencing triggered a compensatory mechanism by overexpressing other genes involved in AA utilization for eicosanoid biosynthesis. Conclusions We concluded that GPAT2 expression is necessary to prevent AA-induced apoptotic cell death in MDA-MB-231 cells and that the overexpression of other AA-metabolizing genes is not sufficient to compensate for the lack of GPAT2 and prevent apoptosis. Keywords GPAT2, Arachidonic acid, Apoptosis, Breast cancer, Cell viability, BNIP3.